Traumatic Impact of Female Genital Mutilation on Individual Well-being in Possessing the Secret of Joy - Sharma, Bimala (Mindscape: A Journal of English & Cultural Studies, 2025)
This paper discusses the psychological trauma faced by people due to the practice of Female Genital Mutilation in Possessing the Secret of Joy. Specifically, the project explores the life of some female characters who were victimized by the ritualistic practice of infibulation in Africa. This research uses the concept of psychological trauma given by Cathy Caruth as the theoretical tool. The research examines the life of Tashi also known as Evelyn, the protagonist of this novel, who undergoes through different psychological phases. She is depressed, terrorized and often had fearful repeated dreams. Later on she is able to recognize the cause of her trauma and the trauma faced by her whole community. The significance of this study is to bring to light the effect of trauma, which could be harmful for the well-being of individuals and for the whole community. It can lead the individual to be violent and even a murderer. In this novel, Tashi feels anxiety and depression in her family life. In the novel, the life of other female characters like Dura, Amy Maxwell and Ayisha is also shown to be affected by the practice of female genital mutilation. This paper concludes that ritual of genital mutilation has devastating effect on life of people by showing several negative impacts of traumatic experience on health, family and social life.